Kewajiban BPJS Kesehatan dalam Pemberian Pelayanan Telekonsultasi Klinis yang Dilakukan Antara Dokter dan Pasien BPJS - Erfandi Dwi Septian (CV WAHANA PUBLIKASI, 2022)
BPJS Health Obligations in Providing Clinical Teleconsultation Services Performed between Doctor and BPJS’ Patients By the decree of the minister of health of the Republic of Indonesia HK.01.07/MENKES/4829/2021 on guidelines of telemedicine utilization to prevent coronavirus disease 2019 (Covid-19). Telemedicine provided by doctors in medical teleconsultation form has been widely considered in this pandemic era. This research uses normative legal research. The approach used in this research is applying the law and the conceptual approach. The result showed various legal norms for BPJS healthcare medical teleconsultation in terms of service. However, BPJS healthcare users are said to be burdened by medical teleconsultation fees, which is different from the initial legal norms. Therefore, it can be said that BPJS has done unlawful acts and is an opening chance for BPJS healthcare users to sue BPJS. Therefore, the researcher recommends that the government make rules regarding the clinical teleconsultation system so that it can run according to its function when needed, for example, during the current covid-19 pandemic. Thus, the task of BPJS in organizing national health insurance for all Indonesian people can be realized. In addition, BPJS Health is required to guarantee the legal protection of patients in clinical teleconsultation services so that the rights and obligations of BPJS participants can be fulfilled. If the rights of the BPJS participants are not fulfilled, the BPJS participants can make mediation efforts. If the mediation mechanism cannot be implemented, the settlement can be submitted to the District Court in the area where the participant lives.